Combined Antiviral and Cytoprotective Action of Rosmarinic Acid Against EV-A71 Infection: A Potential Therapeutic Strategy - Junping Lv; Weishi Lin; Siqi Chao; Jing Xie; Yue Cao; Jinfeng Tie; Yuehua Ke; Binan Lu; Zongran Pang (Pathogens)
Enterovirus A71 (EV-A71), a major etiological agent of hand-foot-mouth disease, can cause severe neurological complications. However, the mechanisms underlying EV-A71-induced cell damage and potential therapeutic strategies remain inadequately understood. Here, we investigated EV-A71 replication dynamics and associated cytopathic effects in nine distinct cell lines, including epithelial, neuronal, immune, and other cell types. Cell viability, membrane integrity, and energy metabolism were assessed using Cell Counting Kit-8 (CCK-8), lactate dehydrogenase (LDH), and adenosine triphosphate (ATP) assays. The antiviral activity of rosmarinic acid (RA), a natural polyphenol, was evaluated by plaque reduction, qPCR, and Western blot. EV-A71 exhibited cell-type-specific replication and cytotoxicity patterns. RA significantly preserved cell viability, reduced LDH release, maintained ATP levels, and suppressed IL-6 expression. Mechanistically, RA inhibited viral replication by downregulating VP1 expression and viral RNA levels. Molecular docking indicated strong binding of RA to the hydrophobic pocket of VP1, potentially disrupting virus-host interactions. Collectively, these findings highlight RA’s combined antiviral and cytoprotective potential, supporting its candidacy as a therapeutic agent against EV-A71 infection.